Colorado Natural Heritage Program: 2017-2022 five-year strategic plan - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2017)
The Colorado Natural Heritage Program (CNHP) is Colorado's key source of information on our natural heritage, which is the nature we have inherited as residents of Colorado. We know that nature is worth a great deal to us, and that our quality of life depends heavily on the condition and diversity of the environment around us. After all, it is the current high quality of our natural world that has made Colorado such a desirable place to live! At CNHP, we keep track of the places we know are tremendously important for conserving our natural wealth and we do this to ensure Colorado remains a great place to live. We map Colorado's rarest animals, plants and ecosystems, and through this work identify the conservation priorities that lead to the best opportunities for safeguarding our natural heritage. Our partners throughout Colorado and beyond count on us to help answer very difficult questions about how conservation can be successful, and our staff of 24 scientists is available to help answer these questions.
2017-2022 five-year strategic plan
Keywords: Colorado Natural Heritage Program; strategic plan